HISTORY AND BASIC PRINCIPLES OF OIL FLOODING (American Journal of Technology and Applied Sciences, 2024)
Although water has been a companion of oil since its formation, the appearance of water in production wells was considered an emergency and the wells were stopped. And only in the late 20s - early 30s of the 20th century it was noticed that more oil was extracted from wells in which water appeared and production was more stable than in waterless wells. In 1932, a commission led by academician. THEM. Gubkin, when analyzing the state of development of fields in the Staro-Groznensky region, established the possibility and effectiveness of displacing oil from reservoirs by contour formation waters. The natural water pressure regime for developing oil deposits was recognized as the most effective.